Battling the known unknowns: a synoptic review of aquatic plastics research from Australia, the United Kingdom and China. Issue 11 (26th October 2021) - Paterson, Harriet L.; Stead, Jessica L.; Crutchett, Thomas; Hovey, Renae K.; Ford, Benjamin M.; Speldewinde, Peter; Zapata-Restrepo, Lina M.; Yanfang, Lu; Zhang, Xiaoyu; Cundy, Andrew B.
Abstract : A synoptic review of aquatic plastics research from Australia, the United Kingdom and China is presented, highlighting (a) key research and management challenges, and (b) a need to converge on standardised methods and bioindicator species to make global comparisons more reliable. Abstract : Plastic pollution is a global environmental and human health issue, with plastics now ubiquitous in the environment and biota. Despite extensive international research, key knowledge gaps ("known unknowns") remain around ecosystem-scale and human health impacts of plastics in the environment, particularly in limnetic, coastal and marine systems. Here we review aquatic plastics research in three contrasting geographic and cultural settings, selected to present a gradient of heavily urbanised (and high population density) to less urbanised (and low population density) areas: China, the United Kingdom (UK), and Australia. Research from each country has varying environmental focus (for example, biota-focussed studies in Australia target various bird, fish, turtle and seal species, while UK and China-based studies focus on commercially important organisms such as bivalves, fish and decapods), and uses varying methods and reporting units ( e.g. mean, median or range). This has resulted in aquatic plastics datasets that are hard to compare directly, supporting the need to converge on standardised sampling methods, and bioindicator species. While all the study nations show plastics contamination, often at high levels, datasets are variable and do not clearly demonstrate pollution gradients.